Digital Transformation Strategies in Primary and Secondary Education Institutions: Case Study of ABC Education Foundation - Khansa Indah Oktaviany (Eduvest - Journal of Universal Studies, 2024)
This research investigates digital transformation strategies to improve the efficiency and competitiveness of ABC Education Foundation in Depok, West Java. Using Sunil Gupta's methodology, this study conducted internal and external SWOT analysis, value chain analysis, business benchmarking analysis, and education technology trend analysis. The findings show that improving information system integration, operational efficiency, and the role of the IT department are key in achieving digital transformation goals. The results also present a digital transformation roadmap based on the stages of value definition, rollout, and improvement. The implications of the digital transformation recommendations can be seen in changes to the business model and organizational infrastructure.